Speech-language Pathologist: A Team Member for Management of Head and Neck Cancer Patients - Bhattarai, Biraj (Nepalese Medical Journal, 2022)
Head and Neck cancer is one of the most prevalent conditions in the world and so is in Nepal. Head and Neck cancer causes speech, language, and swallowing disorder that affects the quality of life of a patient. A multidisciplinary team is needed for the management of the cancer patient. A Speech Language Pathologist is one important team member involved in the rehabilitation of communication and swallowing issues. The role of Speech Language pathologists should be understood by other medical professionals and need to be integrated into the team to provide a holistic health care facility to an individual with head and cancer.